Effect of hyperbaric oxygen therapy on ataxia: A case report - Vicktoria Elkarif; Amir Hadanny; Ruth Tuck Harpaz; Efrat Sasson; Shai Efrati (SAGE Open Medical Case Reports)
Ataxias, a group of disorders characterized by impaired coordination, often lack effective treatments. Recent evidence suggests hyperbaric oxygen therapy (HBOT) may promote neuroplasticity and improve brain function. However, its impact on the core symptom of ataxia remains largely unknown. We present two cases of patients with chronic ataxia of different etiologies who received hyperbaric oxygen therapy. Our findings provide preliminary insights into the potential benefits of hyperbaric oxygen therapy for individuals with chronic ataxia. Two patients, aged 73 and 57, were presented with ataxia characterized by impaired static and dynamic balance, uncoordinated gait, and reliance on walking aids following stroke and brain injury, respectively. Pre and post-treatment evaluation included neuroimaging, gait analysis, and physical/functional assessment. Hyperbaric oxygen therapy treatment was administered for 5 days/week, consisting of 100% oxygen at two atmospheres of absolute pressure. Concurrently, twice-weekly physical therapy sessions were integrated into the treatment regimen. Post-treatment evaluation revealed significant improvements in gait, coordination, and balance, which correlated with perfusion changes in peri-lesional cerebellar tissue as measured by perfusion magnetic resonance imaging. This study presents a pioneering case series exploring the therapeutic potential of hyperbaric oxygen therapy in patients with cerebellar ataxia. Our findings suggest that hyperbaric oxygen therapy may enhance brain perfusion within the peri-lesional region, which correlates with neurophysical improvements. Given the novel nature of these findings, further randomized controlled trials with larger sample sizes and control groups are essential to validate and generalize these findings, ensuring a comprehensive understanding of hyperbaric oxygen therapy’s effects on various brain injuries.